Clinical decision support system for lipid metabolism disorders: relevance and potential - A. S. Alieva; E. I. Pavlyuk; E. M. Alborova; N. E. Zvartau; A. O. Konradi; A. L. Katapano; E. V. Shlyakhto (Российский кардиологический журнал)
Current guidelines for the management of patients with dyslipidemia are well known and easily accessible. Despite this, according to research data based on actual clinical practice, selection of optimal tactics for managing patients with dyslipidemia often causes difficulties and leads to a failure to achieve the target levels. Tools such as clinical decision support system (CDSS) can help clinicians follow current clinical guidelines, taking into account the diversity of phenotypic profiles and side effects. This review highlights the effectiveness of CDSS implementation in medical practice as a means for making decisions in managing patients with dyslipidemia, as well as presents the algorithm for CDSS for lipid metabolism disorders created by specialists of the Almazov National Medical Research Center and the University of Milan.